Identification of novel 2-(1H-indol-1-yl)-benzohydrazides CXCR4 ligands impairing breast cancer growth and motility. (February 2016) - Grande, Fedora; Barone, Ines; Aiello, Francesca; Brancale, Andrea; Cancellieri, Michela; Badolato, Mariateresa; Chemi, Francesca; Giordano, Cinzia; Vircillo, Valentina; Bonofiglio, Daniela; Garofalo, Antonio; Andò, Sebastiano; et al.
Background: Stromal-derived-factor-1 (SDF-1) and the G-protein-coupled receptor CXCR4 are involved in several physiological and pathological processes including breast cancer spread and progression. Several CXCR4 antagonists have currently reached advanced development stages as potential therapeutic agents for different diseases.Results: A small series of novel CXCR4 ligands, based on a 2-(1 H -indol-1-yl)-benzohydrazide scaffold, has been designed and synthesized. The interaction with CXCR4-active site was predicted by molecular docking and confirmed by whole cell-based [ 125 I]-SDF-1 ligand competition binding assays. One of the synthesized compounds was particularly active in blocking SDF-1-induced breast cancer cell motility, proliferation and downstream signaling activation in different breast cancer cell models and coculture systems.Conclusion: The newly synthesized compounds represent suitable leads for the development of innovative therapeutic agents targeting CXCR4.